Co-Creation to Increase Cross-Functional Collaboration in Police Investigations of Online Child Sexual Abuse: A Qualitative Study Protocol - Oscar Rantatalo; Ola Lindberg; Alva Lindholm; Robert Lundmark (International Journal of Qualitative Methods)
This qualitative study protocol outlines a co-creation project between researchers and the Swedish police to improve cross-functional collaboration in online child sexual abuse (CSA) investigations. Online CSA cases are complex and require extensive collaboration between prosecutors, IT forensic expertise, and investigators with expertise in child sexual offenses. Despite the recognized need for cross-functional teamwork, research evaluating methods for such collaboration in crime investigations, especially in online CSA, is scarce. This project, funded by the Swedish research agency FORTE (2023-00085), addresses this gap by employing the ‘double diamond’ co-creation framework (discovery, define, develop, deliver) to co-create, implement, and evaluate a team-based intervention within three online CSA units in northern Sweden. Data collection will involve semi-structured interviews ( n ≈ 35), participant observations of workshops, workshop appraisals, document analysis, and analysis of organizational metrics. The project aims to: (1) identify challenges and potentials for cross-functional teamwork in online CSA investigations; (2) co-design a team-based intervention to address identified needs; and (3) evaluate the intervention’s impact on efficiency and organizational outcomes. By working collaboratively with police practitioners throughout the research process, this project aims to generate practical and sustainable solutions to enhance the effectiveness of online CSA investigations.